PEMANFAATAN PODCAST DAKWAH SEBAGAI MEDIA ALTERNATIF PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Khaidir Khaidir (STAI Nusantara Kota Banda Aceh, 2024)
The digital era presents new opportunities and challenges for the development of Islamic Education (PAI) learning media. One innovative medium that is beginning to be utilised is the dakwah podcast, which is an audio recording containing Islamic messages that can be accessed flexibly through various digital platforms. This study aims to analyse the utilisation of Islamic preaching podcasts as an alternative learning medium for IRE in the digital era, including their advantages, challenges, and implementation strategies. The research method used is library research, reviewing literature related to digital preaching, learning technology, and Islamic education. The results of the study indicate that dakwah podcasts have great potential in improving understanding of Islamic education material due to their accessibility, flexibility, and ability to reach a wide audience. However, content curation strategies, teacher training, and integration with the curriculum are needed for podcasts to function optimally in both formal and non-formal learning. These findings are expected to serve as a reference for educators, school administrators, and digital dakwah activists in developing PAI learning that is adaptive to technological developments.